2014
DOI: 10.1128/aem.01827-14
|View full text |Cite
|
Sign up to set email alerts
|

Axenic Culture of a Candidate Division TM7 Bacterium from the Human Oral Cavity and Biofilm Interactions with Other Oral Bacteria

Abstract: cThe diversity of bacterial species in the human oral cavity is well recognized, but a high proportion of them are presently uncultivable. Candidate division TM7 bacteria are almost always detected in metagenomic studies but have not yet been cultivated. In this paper, we identified candidate division TM7 bacterial phylotypes in mature plaque samples from around orthodontic bonds in subjects undergoing orthodontic treatment. Successive rounds of enrichment in laboratory media led to the isolation of a pure cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 30 publications
3
72
0
1
Order By: Relevance
“…It is obvious that the functional properties of these microorganisms in the oral biofilm environment are of high interest from the clinical and disease prevention perspectives. While one strategy would be to prevent growth conditions favoring detrimental bacteria, other pursuits will require a more detailed knowledge pertaining to the cultivation and cocultivation of all biofilm inhabitants (62)(63)(64)(65). Such insights will be helpful in designing target-specific approaches for the prevention of and/or intervention in diseases exhibiting an oral-biofilm-based etiology.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that the functional properties of these microorganisms in the oral biofilm environment are of high interest from the clinical and disease prevention perspectives. While one strategy would be to prevent growth conditions favoring detrimental bacteria, other pursuits will require a more detailed knowledge pertaining to the cultivation and cocultivation of all biofilm inhabitants (62)(63)(64)(65). Such insights will be helpful in designing target-specific approaches for the prevention of and/or intervention in diseases exhibiting an oral-biofilm-based etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that candidate division TM7 bacteria are detected in biofilm metagenome and this bacterium, when grown in dual species biofilm showed pleiomorphic phenotypes. The TM7 bacteria formed long filaments with A. oris or F. nucleatum but grew as short rod or cocci with P. gingivalis, P. intermedia, P. micra or S. gordonii [80]. Also, the TM7 bacteria were shown to be closely associated with A. oris, F. nucleatum, P. gingivalis, P. intermedia, P. micra and S. gordonii [80].…”
Section: New Candidates and Yet Culturable Bacteriamentioning
confidence: 99%
“…The TM7 bacteria formed long filaments with A. oris or F. nucleatum but grew as short rod or cocci with P. gingivalis, P. intermedia, P. micra or S. gordonii [80]. Also, the TM7 bacteria were shown to be closely associated with A. oris, F. nucleatum, P. gingivalis, P. intermedia, P. micra and S. gordonii [80]. The importance of F. alocis is noted as it is present in high abundance in the periodontal pocket, shows community synergism and is involved in oral biofilm formation with other important periodontopathic bacteria [81,70,82].…”
Section: New Candidates and Yet Culturable Bacteriamentioning
confidence: 99%
“…However, due to their seemingly recalcitrant nature toward cultivation, only one single TM7 phylotype has been reportedly cultivated, with no detailed genomic information (20). Thus, knowledge regarding TM7 genotypes and physiological properties, as well as their potential role in the pathogenesis of oral mucosal disease, is very limited.…”
mentioning
confidence: 99%